Emotional signals from faces, bodies and scenes influence observers' face expressions, fixations and pupil-size - Kret, Mariska E.; Roelofs, Karin; Stekelenburg, Jeroen; de Gelder, Beatrice (Frontiers in Human Neuroscience, 2013)
We receive emotional signals from different sources, including the face, the whole body and the natural scene. Previous research has shown the importance of context provided by the whole body and the scene context on the recognition of facial expressions. This study measured physiological responses to face-body-scene combinations. Participants viewed emotionally (in)congruent face-body and body-scene pairs whilst eye fixations, pupil-size and electromyography (EMG) responses were recorded. Participants focused more on angry and fearful vs. happy or neutral cues, independent of the source and relatively independent from emotional incongruence. Moreover, angry faces combined with angry bodies and angry bodies viewed in an aggressive social scene context elicited greatest pupil dilation. Participants' face expressions matched the valence of the stimuli but when face-body compounds were shown, the observed facial expression influenced EMG responses more than the postures. Our results show that threatening signals from faces, bodies and scenes attract attention, induce arousal, and evoke congruent facial reactions.